PELAKSANAAN EKSEKUSI BARANG BUKTI KASUS PENCURIAN OLEH KEJAKSAAN NEGERI PEKANBARU PASCA PUTUSAN INKRACHT (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
After the court ruling, the execution of evidence of theft cases that in the case of a conviction or free or free from all lawsuits, the court determines that the confiscated evidence is handed over to the party most entitled to receive, namely the party whose name is listed in the decision. Unless according to the provisions of the law, the evidence must be confiscated for the benefit of the country or destroyed so that it can no longer be used.This type of research can be classified as sociological (empirical) Normative legal research. However, although there are elements of field research (sociological) in this study, the data analysis method is carried out with a qualitative approach, because the dominant data used is secondary data or library data with field data as a complement. This research was conducted in the jurisdiction of the Pekanbaru District Attorney's Office. Data sources used are primary data and secondary data. Data collection techniques in this study are the study of literature and interviews.The conclusions that can be obtained from the results of the study are: First, the return of evidence both in terms of procedures and time according to Article 46 paragraph 2 of the Criminal Procedure Code should have been decided, then the evidence (objects) mentioned in the decision must have a clear status, whether returned, seized, or destroyed. Based on article 194 paragraph 3 of the Criminal Procedure Code, an order to hand over evidence is carried out without any conditions. Second, the Legal Procedure in Execution of Evidence of Theft Case by the Pekanbaru District Attorney Office After the Inkracht Verdict, which starts with a case that has received an inkracht decision (a decision that has obtained permanent legal force) and then the judge makes a letter of excerpt, the excerpt of the decision comes out 1 (one) the week after the inkracht verdict Third, the Constraints of the Prosecutor in Execution of Evidence of Theft Case by the Pekanbaru District Prosecutor's Office after the Inkracht Verdict is the person who has been mentioned or explained in the contents of the decision verdict not to take the evidence.Keywords: Execution, Decision, Attorney, Evidence, Criminal Act.